EVALUATION OF PINEAPPLE PEEL ETHANOL EXTRACT CAPSULES AS A NATURAL IMMUNOMODULATOR - Purnamasari M, Vina (PHARMACON, 2024)
Immunomodulators are drugs that can modify immune responses and stimulate natural defense mechanisms. Natural immunomodulator preparations are an alternative solution to using synthetic immunomodulators, because they are safer and have minimal side effects. The immunomodulatory in this research was made from underutilized pineapple skin. This research is focused on finding out the best formulation with varying concentrations of starch as a filler for immunomodulatory preparations from pineapple peel ethanol extract. Research methods include: pineapple peel preparation, extraction of secondary metabolite compounds from pineapple peel with ethanol solvent, phytochemical testing, capsule preparation formulation, and evaluation. Evaluation of capsule preparations: weight uniformity test, disintegration time test, flow velocity test, angle of repose test, and moisture content test. Phytochemical test results show that pineapple peel ethanol extract contains terpenoids, phenolics, flavonoids, alkaloids, steroids and tannins which have potential as immunomodulators. Formulation 1 has test results for angle of response, flow time, stable humidity, uniform weight, and does not break easily. Therefore, formulation 1 (starch 59.58 mg) is the best natural immunomodulator preparation from pineapple peel.